Is the ECI sensitive to the method of aggregation? - Lettau, Michael K.; Loewenstein, Mark A.; Cushner, Aaron (Monthly Labor Review, 1997)
Research by economists at the U.S. Bureau of Labor Statistics suggests that the Employment Cost Index (ECI) is not especially sensitive to the system employed to construct it. The ECI, which is published quarterly, measures fluctuations in the cost of labor—defined as total compensation for each employee-hour worked. ECI wage and benefit indexes reached via geometric cell means generally have lower growth rates than those constructed using arithmetic means. In addition, although alterations in the price of labor can be the result of changes in demand, supply, or both, the standard interpretation implicitly assumes that only one of these factors is changing.